(untitled) (Praxis Educativa, 2021)
This article arises from a variety of research experiences in Chilean schools and is based on a reflection concerning the promotion and practice of Participatory Action Research (PAR) in these schools. Taking into account that adultism prevails in educational establishments, we propose PAR as an intervention strategy that allows the transformation of these relationships through the recognition of students as relevant social actors. Firstly, we describe what PAR is; followed by a description of the Chilean school context. Thirdly, we give an account of the transformations generated by PAR in these schools, reaching our conclusions about the need to take a risk in schools and in the development of this strategy there.